Un-scene III. - Bayar, Devrim; Gray, Zoë (Brussel : Wiels, 2015)
Balcou, Béatrice ; Bernadet, Jean-Baptiste ; Bonin, Sébastien ; Bosmans, Kasper ; Hock, Erika ; Houben, Hedwig ; Kiwitt, Stephanie ; Meert, Julien ; Okumura, Yuki ; Pinsky, Marina ; Slater, Marnie ; Voet, Leen ; Wambacq, freek.
Nederlands
Engels
Frans
tentoonstelling 'Un-scene III', Wiels, Brussel, 30.05.2015 - 09.08.2015.
boek
Keywords: Japan